A new cooperative mechanism for the CMEA? - Klaus Bolz (Intereconomics, 1989)
Dispute as to the need for any thoroughgoing reform of the Council for Mutual Economic Assistance flared up all over again at its 44th Congress in Prague in July 1988. The Soviet Union has now placed itself at the head of the movement for reform but the problems to be faced are considerable and it will take some time for substantial steps to be taken.
Keywords: 330